2019
DOI: 10.4143/crt.2018.010
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Low Absolute CD4+ T Cell Counts May Predict Poor Prognosis in Extranodal NK/T-Cell Lymphoma Patients Treating with Pegaspargase-Based Chemotherapy

Abstract: Low ACD4Cs were associated with poorer survival and could act as a negative predictor for ENKTL patients treated with asparaginase-based regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Extranodal NK/T cell lymphoma (ENKTL) is a unique histopathologic subtype of non-Hodgkin’s lymphoma (NHL), characterized by vascular damage and destruction, necrosis, cytotoxic phenotype, and Epstein–Barr virus (EBV) infection [1]. ENKTL, rare in Europe and North America, is more prevalent in Asia and South America, making up about 5–16% of all NHL patients in China [2]. ENKTL is a highly heterogeneous malignant lymphoma.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extranodal NK/T cell lymphoma (ENKTL) is a unique histopathologic subtype of non-Hodgkin’s lymphoma (NHL), characterized by vascular damage and destruction, necrosis, cytotoxic phenotype, and Epstein–Barr virus (EBV) infection [1]. ENKTL, rare in Europe and North America, is more prevalent in Asia and South America, making up about 5–16% of all NHL patients in China [2]. ENKTL is a highly heterogeneous malignant lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory chemokines and cytokines in tumor microenvironments contribute to the proliferation and survival of malignant cells [6, 7]. Inflammatory indexes such as c-reactive protein (CRP), lymphocyte, and monocyte have been reported to have prognostic values in patients with ENKTL [810]. Lymphocyte is an important biomarker which reflects the host’s immune status, and lymphopenia is associated with a poorer survival in various subtypes of NHL, including ENKTL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying the number of CD4+ T cells, CD8+ T cells, and the CD4+/CD8+ ratio in peripheral blood can thus represent the immunological state of patients with malignant tumors, and it may also be useful in predicting the prognosis of FL patients. The prognostic value of peripheral blood T-lymphocytes has also been reported in patients suffering from various subtypes of lymphoma (32,(40)(41)(42). However, no study has yet precisely reported the prognostic value of the T-cell subset in FL and its added value to clinical prognostic indices that identify patients especially at high risk of early death and progression even after the application of modern immunochemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic in ammation has been demonstrated to be associated with tumor development and progression [11,12]. Absolute lymphocyte counts (ALCs) in the peripheral blood re ect the host immune status [13][14][15][16]. Absolute monocyte counts (AMCs) act as an indicator for tumor-associated macrophages [17,18].…”
Section: Introductionmentioning
confidence: 99%